Desempenho nos testes físicos e força muscular de quadríceps em pacientes com DPOC: uma análise de cluster - Oliveira, Lucas Alves Cassiano de (Universidade Federal de São Carlos, 2020)
Introduction: Individuals with Chronic Obstructive Pulmonary Disease (COPD) present pulmonary and systemic dysfunctions that lead to the loss of peripheral muscle strength and decreased exercise capacity. There is a lack of studies in the literature that characterize clinical behavior through cluster analysis involving these variables, which are important for the development of specific pulmonary rehabilitation programs targeted at these individuals. Objective: To investigate and describe different phenotypes in individuals with COPD according to physical capacity, assessed by the six-minute walk test (6MWT), six-minute step test (6MST), one-minute sit and stand test (1-MSTST) and the quadriceps isometric muscle strength of these individuals. Methods: This is a cross-sectional study, with cluster analysis, in which 55 individuals with stable COPD were subjected to the 6MWT, 6MST, 1-MSTST tests and quadriceps isometric muscle strength test using a hand-held dynamometer. Results: Two phenotypes (A and B) were identified, with phenotype A grouping individuals with better lung function, less dyspnoea, better quadriceps isometric muscle strength and better performance in physical tests (p<0.01 for all variables), in relation to phenotype B. Conclusion: Two phenotypes were identified according to the functional tests and quadriceps isometric muscle strength showing relevant clinical differences that may guide a different therapeutic approach for these individuals.
Performance in physical tests and quadriceps muscle strength in COPD patients: a cluster analysis
Keywords: Fisioterapia; DPOC; Força muscular; Desempenho físico-funcional; Physiotherapy; COPD; Muscle strength; Physical-functional performance; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL